(untitled) (Journal of the College of Basic Education, 2023)
Ferula hermonis Boiss (Apiaceae) is known in the Midleast as "zallouh". In the last decade, scientists paid attention to study chemistry and biological activity of the plant. In this study Ferula hermonis were collected and evaluated for cytotoxic activity. The plant was extracted with methanol The cytotoxic effect of the extracts was examined in-vitro on human cell line (Human liver carcinoma cell line HepG2). Results were shown that significant decrease of HepG2 cells viability. The effect of F. hermonis on cell viability of HepG2 cell line culture show that plant extract cause significant decrease ( p< 0.05) of HepG2 cell viability, and this decrease in cell viability is increased with the increasing the extract concentrations in comparison with the negative control, and the growth inhibition percentage reach to (78.3%). Introduction Ferula hermonis Boiss. (Apiaceae), commonly known as " Shilsh- el-zallouh" , "Hashishat-al-kattira" or "The Lebanese Viagra" ,is a small perennial shrub that grows abundantly at more than 2500 m on the high mountain areas of northern Lebanon, and on the biblical Mount Hermon in Southern Lebanon, (El-Taher et al., 2001). Middle East herbalists have used the seeds and roots of this plant for centuries as a folk remedy as an aphrodisiac to treat frigidity in women, and erectile and sexual dysfunction in men by increasing blood flow to sexual organs. The antimicrobial activity of the crude extract and the isolated compounds has been reported (Hilan et al., 2007). Previous phytochemical studies on this plant have revealed the presence of various sesquiterpenes, mainly of the daucane ester type (Galal et al., 2001). On roots of Ferula hermonis, several sesquiterpenes have been isolated, most of which display biological activities. The active constituents are believed to be daucane alcohols